Analisa peran keimigrasian dalam aspek keamanan negara selama penyelenggaraan presidensi G20 di Indonesia (2022) - Afsari, Ni Luh Putu Intan; I Made Anom Wiranata; Made Lia Agustini (Institute for Advanced Science Social, and Sustainable Future, 2023)
In 2022, Indonesia will have the honor of holding the Presidency of the Group of 20. As the holder of the 2022 Presidency, Indonesia plays an important role in setting the priority agenda and organizing the series of G20 meetings, in which the meeting discusses challenges and issues at the world level. Of course, this momentum was used by Indonesia to show Indonesia's ability to lead global forums, in this case security is one of the priorities in order to create conduciveness for the implementation of these activities. The Directorate General of Immigration as the executor of the task of guarding the gate of the country, which means that immigration is at the forefront in accepting the entry of foreigners into Indonesia by carrying out their duties and functions based on the laws and regulations in force. The research method used by the author is a qualitative method with a literature review approach. The author utilizes optional information to dissect the outcomes, to be specific essential, auxiliary and tertiary materials. The consequences of the review expressed that: The Directorate General of Immigration was available as agent of obligations and capabilities in the field of migration in keeping up with the security of the execution of the G20. The migration capability is the reason for completing the obligations and capabilities did by the Directorate General of Movement. This paper is intended to explain the role of immigration in the aspect of state security; immigration has a vital role in maintaining national sovereignty, especially during the implementation of the G20 Presidency. Keywords: Immigration; G20; State Security